Gingival manifestation of Crohn's disease in a paediatric patient: A case report. (9th November 2021) - Giaccaglia, Francesca; Tomasin, Marco; Angelini, Annalisa; Bacci, Christian
Abstract: Crohn's disease (CD) is a complex multisystemic inflammatory disorder and part of the inflammatory bowel diseases (IBDs). About 20% of the subjects affected by IBDs are paediatric patients and 21% of them present extraintestinal manifestations. Among the extraintestinal manifestations of CD, oral manifestations are rather frequent (20–50% of affected people) and can be difficult to identify, being frequently aspecific and not pathognomonic. Their early diagnosis by the dentist is extremely important, because extraintestinal manifestations can precede intestinal symptoms, in all patients but especially in children. The aim of this paper is to report the case of a CD adolescent patient that presented a gingival manifestation.